UROVAGINAL FISTULA IN TERTIARY HOSPITAL OF WEST JAVA INDONESIA - Karim, Muhammad Ilhamul; Tjahjodjati (Indonesian Journal of Urology, 2022)
Objective: This study was conducted to find out the frequency and characteristics of urovaginal fistula patients. Material & Methods: This study design used a retrospective descriptive research design conducted at a tertiary hospital in West Java, Indonesia (Hasan Sadikin General Hospital) from 1 January 2010 to 31 December 2016. Results: Of all 22 urovaginal fistula patients, the majority in the age range of 41-50 years, and there was one patient in the age range of 61-70 years. Fourteen patients (63.6%) had defects in the bladder, and 36.5% of patients had defects in the ureters. There were nine patients (40.9%) who had urovaginal fistula after undergoing a hysterectomy procedure. The other causes were cervical carcinoma (40.9%), difficult labor (9.1%), radiotherapy (4.5%), carcinoma rectum (4.5%), cesarean section procedure (9.1%), and other gynecological procedures such as myomectomy or cystectomy (9.1%). Based on the type and location of the fistula, the majority of patients had vesicovaginal fistula/VVF (59%), ureterovaginal fistula/UVF (36%), and a combination of ureterovesicovaginal fistula (5%). The causes of VVF and UVF are different from each other. In patients with VVF, the most common cause is cervical carcinoma (35.7%). Meanwhile, the most common cause of UVF is hysterectomy (75%). Conclusion: Of the various types of urovaginal fistulas, vesicovaginal fistulas are the most frequently encountered. In general, the characteristics of urovaginal fistula patients in Hasan Sadikin General Hospital is slightly different from the literature, especially the cause of fistula. At Hasan Sadikin General Hospital, vesicovaginal fistulas are mostly caused by cervical cancer, not a hysterectomy. For ureterovaginal etiology, the characteristics of patients in Hasan Sadikin General Hospital are caused mainly by hysterectomy.